2016
DOI: 10.1128/jvi.02057-15
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of the Core β-Ladder Domain in Japanese Encephalitis Virus Nonstructural Protein 1 Is Flexible for Accommodation of Heterologous Epitope Fusion

Abstract: NS1 is the only nonstructural protein that enters the lumen of the endoplasmic reticulum (ER), where NS1 is glycosylated, forms a dimer, and is subsequently secreted during flavivirus replication as dimers or hexamers, which appear to be highly immunogenic to the infected host, as protective immunity can be elicited against homologous flavivirus infections. Here, by using a trans-complementation assay, we identified the C-terminal end of NS1 derived from Japanese encephalitis virus (JEV), which was more flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, none of the siRNA were carried forward for clinical development. Furthermore, a study by Yen et al, has indicated that NS1 acts as a heterologous epitope and induces a cross-reactive immune response against various pathogens [24]. The NS2A protein has direct involvement in the viral RNA genome synthesis and its assembly and NS2B forms the complex with NS3 and helps in the viral protease activity.…”
Section: Jev Structure and Its Genomementioning
confidence: 99%
“…However, none of the siRNA were carried forward for clinical development. Furthermore, a study by Yen et al, has indicated that NS1 acts as a heterologous epitope and induces a cross-reactive immune response against various pathogens [24]. The NS2A protein has direct involvement in the viral RNA genome synthesis and its assembly and NS2B forms the complex with NS3 and helps in the viral protease activity.…”
Section: Jev Structure and Its Genomementioning
confidence: 99%
“…However, none of the siRNA was carried forward for clinical development. Also, a study by Yen et al, 2015, indicated that NS1 acts as a heterologous epitope and induces a cross-reactive immune response against various pathogens [25]. However, the NS2A protein has direct involvement in the viral RNA genome synthesis and its assembly.…”
Section: Figure 3: Jev Structure Pathogenesis and Potential Drug Targ...mentioning
confidence: 99%
“…The association of NS1 with the membrane and replication complex is mediated through these three distinct structural domains. Yen et al [ 14 ] reported the flexible nature of core β-ladder NS1 protein. JEV NS1 has been reported as a natural viral protein carrier for expressing the heterologous epitopes to stimulate the immune response against various pathogens [ 14 ].…”
Section: Introductionmentioning
confidence: 99%